Pengembangan Kompetensi Profesionalisme Guru di Era Digital (Abad 21) - Notanubun, Zainuddin (Guidance and Counseling Study Program, Pattimura University, 2019)
The development of information and communication technology (ICT) brings change in all lines of life. 21st century Learners live in a digital environment full of information flows. Many negaries reform the objectives and practice of education due to the influence of ICT development and various forms of educational innovation. The greatest hope of educational innovation is the support and integration of ICT in the learning process, thus enhancing the quality of student learning experience. The characteristics of 21st century students are very different from previous era students. In the 21st century one must have four skills (communication, colaboration, critical Thinking and problem Sorving and Creativity and Innovation). This skill has always been reflected in the learning that will be implemented by a professional teacher, by having the competence of pedagogic, professional, personality, and social competence